2007
DOI: 10.1002/j.0022-0337.2007.71.2.tb04269.x
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Dental Ethicists and the Promise of Universal Patient Acceptance: Response to Richard Masella's “Renewing Professionalism in Dental Education”

Abstract: Richard Masella's "Renewing Professionalism in Dental Education: Overcoming the Market Environment" reveals why professionalism is nearly dead in America; it also shows the good of commerce and the excesses of commercialism in the market. More importantly, it collects and summarizes most of the relevant forms of education currently available to teach professionalism and professional ethics in dentistry; it then briefly examines whether those forms of education are used and if they are effective. Masella also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…(Lyons 1983, p. 16) The concern that professionalism in dentistry is being eroded by commercialism has been echoed since by many others. Notable contributions include Masella's (Masella 2007) statement on the need to overcome the market environment of practice, Botto's (Botto 2007) anxieties around the proliferation of the market mentality within dental practice, and Patthoff's (Patthoff 2007) statement of a need for more ethical discussion within the profession to combat excesses of commercialism. Chambers (2006) considers that commercialism may have brought positive advances to the practice of dentistry.…”
Section: Commercialism Versus Professionalism: a Need For A Reviewed Approach?mentioning
confidence: 99%
“…(Lyons 1983, p. 16) The concern that professionalism in dentistry is being eroded by commercialism has been echoed since by many others. Notable contributions include Masella's (Masella 2007) statement on the need to overcome the market environment of practice, Botto's (Botto 2007) anxieties around the proliferation of the market mentality within dental practice, and Patthoff's (Patthoff 2007) statement of a need for more ethical discussion within the profession to combat excesses of commercialism. Chambers (2006) considers that commercialism may have brought positive advances to the practice of dentistry.…”
Section: Commercialism Versus Professionalism: a Need For A Reviewed Approach?mentioning
confidence: 99%
“…For dental educators, professionalism includes the often implied values, virtues, and characteristics that guide the practice of dentistry in the promotion of oral health. [2][3][4][5] For patients, professionalism is defined by the demonstration of excellence and effective communication skills, commitment to humanism and service, and perceived clinical competence in the form of effective management of duties, and skills. 6 For dental hygiene students in Japan, professionalism was perceived, in their cultural context, as a multifaceted judgment of intrapersonal, interpersonal, and public professionalism.…”
mentioning
confidence: 99%
“…An examination of how the academic literature in dentistry reconciles this relationship between professional and commercial obligations exposed a lack of empirical exploration of this tension 2 . Commentaries on commercialism in dentistry have suggested that commercialism is a negative influence, citing issues such as predatory advertising, 3 increased professional competition 4,5 and a transactional attitude to care 6 as chief concerns. A transactional attitude to the provision of care differs from the dynamic of the accepted professional paradigm established within the dentist‐patient relationship.…”
Section: Introductionmentioning
confidence: 99%